Mid-Thoracic Spinal Injuries during Horse Racing: Report of 3 Cases and Review of Causative Factors and Prevention Measurements - Ioannis Triantafyllopoulos; Andreas Panagopoulos; George Sapkas (Case Reports in Orthopedics)
We report three cases of a rare pattern of mid-thoracic spine injuries after horse racing falls and discuss possible causative factors and prevention measurements to reduce injury rates in professional riding and racing. Three patients, 2 male and 1 female with a mean age of 28 years old, underwent surgical treatment for mid-thoracic fractures after professional equestrian activities. The ASIA scale was E in one patient, B in the other one and A in the third. Multilevel posterior fusion was used in two patients and somatectomy plus fusion in the other. Follow up evaluation included changing of the ASIA scale, functional outcome and participation in equestrian activities. One patient fully recovered after surgery. Two patients remained paraplegic despite early surgical treatment and prolonged rehabilitation therapy. All patients had ended their professional equestrian career. This report analyzes possible mechanisms of injury and the pattern of mid-thoracic spine fractures after professional horse riding injuries. Despite skill improvements and continued safety education for horse riding, prophylactic measures for both the head and the spine should be refined. According to our study, additional mid-thoracic spinal protection should be added.